Service quality factors effecting customer's behavioral intentions towards Selesa Beach Resort, Port Dickson / Siti Zubaidah Bakri - Bakri, Siti Zubaidah (Faculty of Business and Management, 2007)
The purpose of this study was to assist Selesa Beach Resort, Port Dickson in improving their service quality towards increasing the customer loyalty. The results of this study illustrate to develop a clear understanding on the dimensions of service quality in the context of Selesa Beach Resort, Port Dickson. Furthennore, it would help to identify the factors affecting the customer's behavioral intentions towards Selesa Beach Resort, Port Dickson. The study is hoped to suggest several methods that could be taken to improve the service quality that could be used as an input in designing customer retention strategies. The researcher investigated the degree to which behavioral intentions could be explained by service quality dimensions. Zeithaml et's (1996) theoretical framework was used to measure behavioral intentions while the five dimensions of SERVQUAL were used to measured perceived service quality. A total of 80 customers of Selesa Beach Resort, Port Dickson participated in this study.